2003
DOI: 10.1128/aac.47.5.1727-1731.2003
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Salmonellae in Blood and Bone Marrow: Randomized Controlled Trial Comparing Ciprofloxacin and Chloramphenicol Treatments against Enteric Fever

Abstract: We performed a randomized controlled trial involving 55 adult patients with enteric fever to compare ciprofloxacin and chloramphenicol. Blood and bone marrow cultures and cytokine profiles during therapy were done to compare the clinical and bacteriological efficacies of these drugs. All patients were randomly assigned to receive chloramphenicol (500 mg four times a day orally) for 14 days or ciprofloxacin (500 mg twice a day orally) for 7 days. In each treatment group, patients were subsequently randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…It would be interesting to define whether B lymphocytes mediate Salmonella transit from intestinal wall to spleen, liver, or bone marrow, the main targets for Salmonella persistence (13,20,26,56). In fact, it has been demonstrated that activated B lymphocytes travel from lymphoid organs to bone marrow to become antibody-producing cells.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to define whether B lymphocytes mediate Salmonella transit from intestinal wall to spleen, liver, or bone marrow, the main targets for Salmonella persistence (13,20,26,56). In fact, it has been demonstrated that activated B lymphocytes travel from lymphoid organs to bone marrow to become antibody-producing cells.…”
Section: Discussionmentioning
confidence: 99%
“…The succinate ester prodrug is used for intravenous or intramuscular administration and gives lower serum levels than the oral form (436,437). Chloramphenicol has been shown to be clinically effective in a number of studies (341,(438)(439)(440)(441)(442)(443)(444)(445)(446)(447). Disadvantages of chloramphenicol are its four-times-daily administration and the need to give it for at least 2 weeks to reduce the 10 to 15% risk of relapse.…”
Section: Traditional First-line Antimicrobialsmentioning
confidence: 99%
“…Ciprofloxacin is a broad-spectrum antimicrobial that is used in the treatment of numerous infectious diseases, including those afflicting the skin (Lipsky et al, 1999), bone (Gasem et al, 2003), gastrointestinal tract (Hsieh et al, 1998), genitourinary system (Wagenlehner et al, 2006), lungs (Jones, 2002), and meninges (Gogos et al, 1991). It is also a preferred agent for the prevention and treatment of anthrax (Meyerhoff et al, 2004).…”
mentioning
confidence: 99%